Structural characteristics and diversity of the rhizosphere bacterial communities of wild Fritillaria przewalskii Maxim. in the northeastern Tibetan Plateau - Cui, Zhijia; Li, Ran; Li, Fan; Jin, Ling; Wu, Haixu; Cheng, Chunya; Ma, Yi; Wang, Zhenheng; Wang, Yuanyuan (Frontiers in Microbiology, 2023)
Introduction Fritillaria przewalskii Maxim. is a Chinese endemic species with high medicinal value distributed in the northeastern part of the Tibetan Plateau. F. przewalskii root-associated rhizosphere bacterial communities shaped by soil properties may maintain the stability of soil structure and regulate F. przewalskii growth, but the rhizosphere bacterial community structure of wild F. przewalskii from natural populations is not clear. Methods In the current study, soil samples from 12 sites within the natural range of wild F. przewalskii were collected to investigate the compositions of bacterial communities via high-throughput sequencing of 16S rRNA genes and multivariate statistical analysis combined with soil properties and plant phenotypic characteristics. Results Bacterial communities varied between rhizosphere and bulk soil, and also between sites. Co-occurrence networks were more complex in rhizosphere soil (1,169 edges) than in bulk soil (676 edges). There were differences in bacterial communities between regions, including diversity and composition. Proteobacteria (26.47–37.61%), Bacteroidetes (10.53–25.22%), and Acidobacteria (10.45–23.54%) were the dominant bacteria, and all are associated with nutrient cycling. In multivariate statistical analysis, both soil properties and plant phenotypic characteristics were significantly associated with the bacterial community (p < 0.05). Soil physicochemical properties accounted for most community differences, and pH was a key factor (p < 0.01). Interestingly, when the rhizosphere soil environment remained alkaline, the C and N contents were lowest, as was the biomass of the medicinal part bulb. This might relate to the specific distribution of genera, such as Pseudonocardia, Ohtaekwangia, Flavobacterium (relative abundance >0.01), which all have significantly correlated with the biomass of F. przewalskii (p < 0.05). Discussion F. przewalskii is evidently averse to alkaline soil with high potassium contents, but this requires future verification. The results of the present study may provide theoretical guidance and new insights for the cultivation and domestication of F. przewalskii.